Teachers’ Computer Capacity in Public Primary Schools in Homa Bay County, Kenya: The Case of the Digital Literacy Programme - Ouma Omito; Jane Kembo; Mildred Ayere; Ali Adan Ali (European Scientific Journal, ESJ, 2019)
Kenyan public primary schools are rapidly adopting digital technology in teaching and learning. The purpose of this study was to establish teachers’ computer skills as groundwork towards the integration of laptop computers in public primary schools in Homa Bay County, Kenya. The study was based on one objective: to investigate the teachers’ computer skills that were necessary for the Digital Literacy Programme (DLP) in Homa Bay County. A crosssectional survey was adopted asthe research design whereby both quantitative and qualitative research data were collected and used for the study. The study population comprised of 6,529 teachers and 845 head teachers in public primary schools in Homa Bay County. A sample size of 362 teachers and 85 head teachers were used for the study. Data were collected using questionnaires and interview schedules. Quantitative data were analyzed using descriptive statistics. The results from the interviews were recorded, transcribed, organized into major themes and reported. The findings showed that 199 (56.4%) sample teachers had attended general computer literacy courses at various institutions of learning. The study also showed that 109 (30.9%) of the sampled teachers had been trained by the government on DLP. However, when the teachers’ computer skills were rated on a 5-point Likert scale, they were found to be low (2.76). In addition, 35 (44.3%) of the sampled schools had no teacher trained in computer skills by their colleagues as was expected. The study concluded that sample teachers had a good starting point for computer skills training which only needed to be strengthened by the government.